INDIVIDUALLY ADAPTED CURRICULUM FOR INCLUSIVE EDUCATION - Farid Alamdar oglu Suleymanov (Russian State Vocational Pedagogical University, 2015)
The aim of this study is to analyse and discuss, with regard tothe Curriculum Relation Model proposed by Berit Johnsen, how to plan a meaningful and individually adapted curriculum related to class curriculum as a means to realise the international principle of inclusive education.Methods. The methods involve scientific and pedagogical analyses of one of the recent and sophisticated theories relating to the best model of an adapted curriculum and literature review for the international principle of inclusive education.Results. Detailed investigation of Curriculum Relation Model reveals that this model involves all relevant aspects which should be taken into consideration when curriculum needs adaptation within inclusive education setting all over the world. An extension of the model with all the relevant aspects (the pupil/s, educational intentions, educational content, methods and organisation, assessment, communication, care and context/frame factors) makes it an ideal tool for a teacher/special needs educator to plan meaningful and individually adapted curriculum with a full relation to class curriculum. As for the international principle of inclusive education, literature review suggest that there are several international declarations and other relevant documents proposed by the United Nations regarding the rights of children with special needs to quality education without being exposed to any kinds of discrimination.Scientific novelty. Scientific novelty of the study involves a fresh innovation in the sphere of curriculum development which still keeps its importance urgency in the countries initiating reforms in education.Practical significance. Currently, inclusive education is an intensively discussed issue almost in all the countries. Although inclusive education has a history of couple of decades, some countries are at the beginning of inclusive education initiation. This is a point they come across quite a lot challenging issues one of which is the proper and effective adaptation of the curriculum. From this perspective, Curriculum Relation Model proposes a brilliant idea.